Security and Privacy in Communication Networks : 11th EAI International Conference, SecureComm 2015, Dallas, TX, USA, October 26-29, 2015, Proceedings - Thuraisingham, Bhavani; Wang, XiaoFeng; Yegneswaran, Vinod; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume constitutes the thoroughly refereed post-conference proceedings of the 11th International Conference on Security and Privacy in Communication Networks, SecureComm 2015, held in Dallas, TX, USA, in October 2015. The 29 regular and 10 poster papers presented were carefully reviewed and selected from 107 submissions. It also presents 9 papers accepted of the workshop on Applications and Techniques in Cyber Security, ATCS 2015. The papers are grouped in the following topics: mobile, system, and software security; cloud security; privacy and side channels; Web and network security; crypto, protocol, and model.
Keywords: Computer security; Computer science; Computer Communication Networks; Data encryption (Computer science).; Systems and Data Security; Computers and Society; Computer Communication Networks; Cryptology